2020
DOI: 10.3390/w12041163
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sponge City Construction for Reducing Directly Connected Impervious Areas on Hydrological Responses at the Urban Catchment Scale

Abstract: Low-impact development (LID) has been widely used at both site-specific and local scales to try and mitigate the impact of urban stormwater runoff caused by increasing impervious urban areas. Recently, the concept of a “sponge city” was proposed by the Chinese government, which includes LID controls at the source, a pipe drainage system midway, and a drainage system for excess stormwater at the terminal. There is a need to evaluate the effectiveness of sponge city construction at the large urban catchment scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Samouei and Zger [23] investigated the hydrologic response of the catchment after replacing proportions of impervious surfaces with combinations of LID practices, and the results showed that implementing 5-20% of LIDs has a noticeable impact on runoff peak flow and volume reduction, especially in storm events with shorter return periods. Liang et al [24] studied the performances of five design scenarios with different spatial distributions, but with the same sizes of LID controls, at the urban catchment scale, and the results confirmed that the hydrological performance was more sensitive to rainfall intensity along with the rainfall intensity increased.…”
Section: Introductionmentioning
confidence: 94%
“…Samouei and Zger [23] investigated the hydrologic response of the catchment after replacing proportions of impervious surfaces with combinations of LID practices, and the results showed that implementing 5-20% of LIDs has a noticeable impact on runoff peak flow and volume reduction, especially in storm events with shorter return periods. Liang et al [24] studied the performances of five design scenarios with different spatial distributions, but with the same sizes of LID controls, at the urban catchment scale, and the results confirmed that the hydrological performance was more sensitive to rainfall intensity along with the rainfall intensity increased.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, studies related to improving the accuracy, efficiency, and robustness of hydrological models have been highlighted (Pang et al, 2020;Yin et al, 2020;Tang et al, 2021). Moreover, these stormwater management models are increasingly coupled with other platforms or models to achieve more comprehensive functions or to run simulations at larger spatial scales (Duan and Gao, 2019;Liang et al, 2020;Xu et al, 2021). Hydrological models were also integrated with remote sensing techniques, and neural networks have become more popular Wu Z et al, 2021).…”
Section: Social Benefitsmentioning
confidence: 99%
“…LID facilities with small land occupation and low-cost maintenance with enhanced water quality of aquatic habitat are most suitable for urban residential areas. Additionally, residential areas have a large number of individual buildings and abundant green spaces, for which LID facilities can be used to improve the status of stormwater management and enhance the multiple ecological effects of the landscape, such as flooding mitigation and pollution reduction [15,16]. As the residential area can be an important practice object for Sponge City renovation, it will promote to build the whole city as a "big sponge" through the construction of green stormwater infrastructures in many residential areas called "small sponge".…”
Section: Introductionmentioning
confidence: 99%